A taxonomy of ecopreneurship in small manufacturing firms: A multidimensional cluster analysis. (22nd November 2020) - Ljungkvist, Torbjörn; Andersén, Jim
Abstract: This study presents a multidimensional taxonomy of "ecopreneurship" for small manufacturing firms. Based on a cluster analysis of 312 Swedish firms, four distinct clusters are identified: pioneers, green dumpers, overlookers, and recyclers. These clusters are compared regarding their level of entrepreneurial orientation and firm performance. Based on the results, and because of the resource constraints associated with small firms, managers of such companies are advised to examine the economic consequences of specific environmental business practices and to adopt a less aggregated approach to ecopreneurship. This study illustrates the usefulness of a multidimensional scale when researching environmental behaviors and is a response to the lack of an empirically based classification of ecopreneurship configurations.